Meningkatkan Kemampuan Berpikir Kritis Siswa Melalui Media Mistery Box Pada Pelajaran Bahasa Indonesia - Silva Novia; Muhammad Sabli; Selvia Nelis (Varied Knowledge Journal, 2026)
This study was motivated by the low critical thinking skills of second-grade students at Sekolah Dasar Alam Muara Bungo in Indonesian language learning. Students were still less active in asking questions, had difficulty expressing opinions, and were unable to provide logical answers because the learning process was still teacher-centered and lacked engaging learning media. This study aimed to improve students’ critical thinking skills through the use of Mystery Box learning media. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects of this study were second-grade students of Sekolah Dasar Alam Muara Bungo. Data were collected through observation, tests, documentation, and field notes. The results showed an improvement in students’ critical thinking skills in each cycle. In the pre-cycle stage, learning mastery only reached 40%. After the implementation of the Mystery Box media in Cycle I, it increased to 60%, and further improved to 90% in Cycle II. Students became more active in asking and answering questions, expressing opinions, and providing simple reasons for their answers. Therefore, the use of Mystery Box media was effective in improving students’ critical thinking skills in Indonesian language learning.